QUANTIFICATION OF ALTERATION IN MINERAL CONTENTS OF DIFFERENT CITRUS GENOTYPES WITH VARYING DISEASE RESPONSES INDUCED BY ELSINOE FAWCETTII - Usama Ahmad; Shahbaz Talib Sahi; Muhammad Atiq; Muhammad Ahsan Khan (Journal of Animal and Plant Sciences, 2026)
The objective of the study was to determine the resistance of citrus cultivars to citrus scab (Elsinoe fawcettii) and to examine the effects of infection on mineral composition of the leaves. Regardless of the significant economic impact of scab disease, limited comparisons of citrus cultivars to scab disease taken across multiple cultivars and a lack of understanding of nutrient composition in relation to disease severity exists. Citrus (Citrus spp.) comprises various species of fruit crops that have world significance and are extensively grown in tropical, subtropical and Mediterranean climates. Its productivity is adversely affected by a fungal disease citrus scab caused by Elsinoe fawcettii. This research was conducted in a randomized completely blocked design (RCBD) with three replicates to evaluate the resistance levels of twenty citrus varieties against scab disease and to investigate changes in mineral contents between healthy and diseased leaves. Disease severity was measured on a 0-5 scale and analyzed through ANOVA, means were compared through Tukey HSD comparisons to determine differences at p ≤ 0.05. Field evaluation of the cultivars over three consecutive growing seasons (2020–2022) revealed statistically significant variation in disease response. Among the twenty citrus cultivars, Citrus japonica ‘Kumquat’, Citrus reticulata ‘Kinnow’ and Citrus paradisi ‘Duncan’ exhibited high levels of resistance with disease severities of 0.71%, 1.75% and 3.92%, respectively. Highly susceptible cultivars showed the greater disease severity, such as Citrus sinensis ‘Jaffa’ (27.48%), Citrus sinensis ‘Ruby Red’ (28.59%), Citrus paradisi ‘Foster’ (30.02%), Citrus paradisi ‘Shamber’ (31.95%) and Citrus sinensis ‘Valencia Late’ (34.00%). Mineral analysis, conducted by using spectrophotometric and flame emission methods, revealed marked reductions in key elements in infected leaves compared to healthy ones. Nitrogen content declined from 10.70% in healthy ‘Red Blood’ leaves to 2.16% in infected ‘Feutral’s Early’; phosphorus decreased from 2.84% in healthy ‘Red Blood’ to 0.09% in infected ‘Feutral’s Early’; and potassium dropped from 12.70% in healthy ‘Red Blood’ to 2.86% in infected ‘Feutral’s Early’. Similar reductions were also observed in calcium, magnesium, sodium, zinc, iron and copper. These findings highlight that mineral depletion increases with disease severity, as it disturbs the nutritional uptake in citrus. The results highlight that integrating resistant cultivars with balanced nutrient management can substantially reduce citrus scab incidence and associated yield losses.
Keywords: Citrus; Cultivars; Citrus Scab; Disease Resistance; Elsinoe fawcettii; Minerals Alteration